Assessing the National Population Commission’s Communication Techniques for Census Engagement with Lagos Residents - Oyesomi, Kehinde; Fasakin, Olarenwaju (Covenant Journal of Communication, 2025)
The research assesses the communication techniques that were used by the National Population Commission (NPC) to involve the residents of Lagos in the process of the national population census. The research focuses on the multi-ethnic and densely populated Lagos State, and uses in-depth qualitative interviews with pertinent officials of the Nigeria Population Commission (NPC) and Lagos State Ministry of Information and Orientation. The results identify the development of a wide multi-channel communication plan that combines multilingual messages delivered through traditional mass channels of communication, Community outreach to key opinion formers, informal town criers, and market rallies, in addition to the use of social media influencers and social media. The research indicates high socio-cultural barriers such as cultural resistance to enumeration, the migration process of the census, and misunderstanding about the census intention, which influence the attitude and response to the census. The role played by NPC, trial censuses, pilot surveys, and strategic involvement of influential community members will be crucial in improving the level of understanding and trust. The framework of communications implies participatory and two-way communication models principles, which illustrate the significance of culturally sensitive, inclusive, and adaptive approaches in embracing census participation. The research recommends the importance of perpetual innovation, multi-linguality, and continuous review to maintain and streamline public participation in subsequent census activities in Lagos, which is one of the major challenges to success in the accurate collection of data to enable efficient governance and resource distribution to occur in Nigeria